2011
DOI: 10.1540/jsmr.47.79
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omeprazole on gastric myoelectrical activity and emptying

Abstract: Omeprazole, a proton pump inhibitor, is widely used for the treatment of patients with peptic ulcer, gastroesophageal reflux disease and functional dyspepsia (FD), although some studies have demonstrated that omeprazole delays gastric emptying. The purpose of this study was to investigate the efficacy of omeprazole on gastric motility including gastric myoelectrical activity and gastric emptying. This study was performed on 12 healthy volunteers. Gastric motility was evaluated with cutaneously recorded electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…However, in this study, in relation to the animals treated with THERM (100 ​mg/kg), pretreatment with omeprazole (20 ​mg/kg), a proton pump (H + ,K + -ATPase) inhibitor, did not affect the reduction of THERM-induced emptying (30.5 ​± ​3.0% vs. 35.5 ​± ​6.3%, P > 0.05). Moreover, as described by Kamiya et al. (2011) , we found that pretreatment with omeprazole did not interfere in GE (50.2 ​± ​2.6% vs. 56.6 ​± ​3.6%, P > 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…However, in this study, in relation to the animals treated with THERM (100 ​mg/kg), pretreatment with omeprazole (20 ​mg/kg), a proton pump (H + ,K + -ATPase) inhibitor, did not affect the reduction of THERM-induced emptying (30.5 ​± ​3.0% vs. 35.5 ​± ​6.3%, P > 0.05). Moreover, as described by Kamiya et al. (2011) , we found that pretreatment with omeprazole did not interfere in GE (50.2 ​± ​2.6% vs. 56.6 ​± ​3.6%, P > 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…These effects of omeprazole may be one of the mechanisms involved in its efficacy in relieving dyspeptic symptoms in patients with functional dyspepsia [90]. …”
Section: Validation Of Eggmentioning
confidence: 99%
“…This has to be addressed in further studies. Although one study showed that administration of omeprazole did not affect gastric motility, 23 we cannot fully rule out that proton pump inhibitors can influence gastric emptying and gastric symptoms.…”
Section: Discussionmentioning
confidence: 86%